The Influence of Motivation, Organizational Culture, and Transformational Leadership Style on Performance at Bhaktiasih General Hospital - Mohammad Abubakar; Sandra Dewi; Arrozi MF. (Jurnal Indonesia Sosial Sains, 2024)
This study investigates the influence of motivation, organizational culture, and transformational leadership style on performance at Bhaktiasih General Hospital. Utilizing quantitative analysis methods, data was collected from employees through surveys and analyzed using regression analysis. The results revealed significant positive effects of motivation, organizational culture, and transformational leadership style on employee performance with simultaneous test F count (318.779) > F table (2.16), significance of 0.001 less than 0.10 and coefficient of determination of 0.823 or 82.30%. Specifically, higher levels of motivation, a strong organizational culture, and effective implementation of transformational leadership were associated with improved performance outcomes. These findings underscore the importance of fostering a motivational work environment, nurturing a positive organizational culture, and adopting transformational leadership practices to enhance performance in healthcare settings. Understanding these factors can inform management strategies aimed at improving overall performance and quality of care in hospitals like Bhaktiasih General Hospital.